Safety analysis of a Vero-cell culture derived Japanese encephalitis vaccine, IXIARO ® (IC51), in 6 months of follow-up - Dubischar-Kastner, Katrin; Kaltenboeck, Astrid; Klingler, Anton; Jilma, Bernd; Schuller, Elisabeth (Vaccine, 2010)
Japanese encephalitis (JE) is the most common viral encephalitis in Asia. IXIARO ® is a Vero cell-derived, inactivated JE virus vaccine which has recently been approved in the US, Europe, Canada and Australia (trade name JESPECT). This overview of the safety and tolerability of IXIARO ®, for 6 months after the first vaccination in 7 Phase III trials, includes: 3558 subjects with at least one IXIARO ® vaccination, 435 subjects with a JE-VAX ® (manufactured by BIKEN, distributed by Sanofi Pasteur) vaccination, and 657 with phosphate-buffered saline solution with 0.1% Al(OH) 3 (PBS + Alum) control vaccination. The percentage of subjects reporting solicited local adverse events (AEs) with IXIARO ® (54%) was similar to PBS + Alum vaccination (56%) as were solicited systemic adverse events (40% IXIARO ®; 40% PBS + Alum vaccination). JE-VAX ® showed a higher frequency of subjects with solicited local adverse events (61%) but a slightly lower frequency of subjects with solicited systemic adverse events (36%). The frequency of subjects with any solicited and unsolicited AE with IXIARO ® (64%) was also similar to PBS + Alum vaccination (61%) and JE-VAX ® (64%); as for subjects with serious AEs (1% IXIARO ®; 2% PBS + Alum vaccination, 1% JE-VAX ®). No serious allergic reactions were observed in any group. This safety analysis indicates that IXIARO ® has a favorable safety profile, comparable to PBS + Alum control vaccination and appears to have a better local tolerability profile than JE-VAX ®.